PERENCANAAN DALAM PENDIDIKAN - AISYAH Aisyah (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2018)
Abstract: This paper discusses planning in education. Educational planning is the basis of implementation in education by looking at the future that will be done to develop order to be more effective and efficient in accordance with the needs of the community to achieve development targets, which can be relied upon. Good planning must be able to provide answers to the concept of questions formulated in six questions, namely: what, why, where, when, who, what, what will be planned. The type in the process can be used in terms of time, namely the long term, win and short term planning, based on scope, macro, meso, and micro, as well as approaches based on education levels. The planning process starts from the preparation of program plans, implementation of plans, supervision and evaluation.Through good planning in education, the results that are expected to achieve.Keywords: Planning and education